VIAȚA ȘI ACTIVITATEA ȘTIINȚIFICĂ A DR. EUGEN KOZAK, PROFESOR ȘI PREOT, RECTOR AL UNIVERSITĂȚII DIN CERNĂUȚI* (I) - Чучко, Михайло Костянтинович; Chuchko, Mykhailo; Грябан, Вікторія Вікторівна; Hryaban, Viktoriya (Analele Bucovinei, XXXII, 2 (65), p. 347–378, Rădăuți – Bucureşti, 2025, 2025)
The article is dedicated to the figure of the prominent Slavic studies scholar, rector of Chernivtsi University, religious and socio-political figure, senator, archpriest-stavrophore, professor, and Doctor of Philosophy, Eugen Kozak (1857–1933). Born into a large family of an Orthodox priest, after finishing gymnasium, E. Kozak obtained a theological education at Chernivtsi University and studied philology at the University of Vienna. After defending his doctoral dissertation in Slavic studies in Vienna, throughout his life he combined philological research with ecclesiastical service. A student of the renowned Slavicist Vatroslav Jagić, Professor E. Kozak headed the Department of Church Slavonic Language and Literature at the Orthodox Theological Faculty of Chernivtsi University, served as the dean of that faculty, and was rector of the university. As a researcher, E. Kozak made a significant contribution to the development of Slavic studies, publishing works on Slavic epigraphic monuments, the materials of which still retain scholarly value today. His most well-known work was dedicated to ancient inscriptions from churches and monasteries in Bukovina.
Life and Scientific Research of Dr. Eugen Kozak, Professor and Priest, Rector of Chernivtsi University (I). Analele Bucovinei, XXXII, 2 (65), p. 347–378, Rădăuți – Bucureşti, 2025
articl
Keywords: Eugen Kozak, Chernivtsi University, professor, rector, dean, Slavicist, priest, theological faculty, Church Slavonic language, epigraphic monuments, Bukovina, Metropolis.